Efficient routes toward the synthesis of the D-rhamno-trisaccharide related to the A-band polysaccharide of Pseudomonas aeruginosa - Aritra Chaudhury; Sajal K. Maity; Rina Ghosh (Beilstein Journal of Organic Chemistry, 2014)
The present work describes efficient avenues for the synthesis of the trisaccharide repeating unit [α-D-Rhap-(1→3)-α-D-Rhap-(1→3)-α-D-Rhap] associated with the A-band polysaccharide of Pseudomonas aeruginosa. One of the key steps involved 6-O-deoxygenation of either partially or fully acylated 4,6-O-benzylidene-1-thiomannopyranoside by radical-mediated redox rearrangement in high yields and regioselectivity. The D-rhamno-thioglycosides so obtained allowed efficient access to the trisaccharide target via stepwise glycosylation as well as a one-pot glycosylation protocol. In a different approach, a 4,6-O-benzylidene D-manno-trisaccharide derivative was synthesized, which upon global 6-O-deoxygenation followed by deprotection generated the target D-rhamno-trisaccharide. The application of the reported regioselective radical-mediated deoxygenation on 4,6-O-benzylidene D-manno thioglycoside (hitherto unexplored) has potential for ramification in the field of synthesis of oligosaccharides based on 6-deoxy hexoses.